PENGARUH PROGRAM TEACHING FACTORY (TEFA) & KOMPETENSI PRODUK KREATIF DAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMKN 4 PEKANBARU - Amalina, Zahratu; Sumarno, Sumarno; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know the influence of teaching factory (TEFA) & the competence of creative products and entrepreneurship SMKN 4 Pekanbaru. The population in this research is a student of batik craft Program and textile SMKN 4 Pekanbaru as many as 89 people and in this research will be taken as a whole from the population referred to as the saturated samples. Data collected using primary data is a questionnaire about the teaching factory Program, entrepreneurial interests distributed to respondents and secondary data, namely the documentation. Data analysis using path analysis. The results of a descriptive analysis of the study explained that the interest of entrepreneurial students in high category because of teaching factory is implemented in good category and competency of creative product and entrepreneurship as much as 91.2% in category Competent. As for the analysis of the program path of teaching factory directly positively affect the competency of creative products and entrepreneurship of 0.236. The teaching factory Program directly affects the student's entrepreneurial interest of 0.214 and indirectly at 0.066 for a total of 0.280. The competency of creative products and entrepreneurship directly positively affects the entrepreneurial interest of 0.282. The competency of creative products and entrepreneurship directly positively affects the entrepreneurial interest of 0.282. With this research, the school should further improve the existing teaching factory program so that it can improve the competency of students and also can increase the entrepreneurial interest of students.Key Words: Teaching Factory Program, Creative And Entrepreneurial Product Competency, And Entrepreneurship Interest.